2013
DOI: 10.4236/jwarp.2013.54a001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation as a Water Resource Policy Challenge —Institutions and Science

Abstract: Adaptation is the pursuit of active, deliberate measures to enhance humankind's capacity to manage water supply and attenuate demand in the face of climate uncertainty. This article contends that worsening constraints upon freshwater due to climate variability demand concerted, imaginative, science-based solutions. These solutions must join creative management to co-production of climate knowledge. Through a series of case studies, we analyze the need for adaptation approaches to prevail over climate variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Quantification of water pollution sources during hydrologically different situations is indispensable for adopting particular protective measures in various landscape zones and for setting the effective agricultural land management . However, findings obtained in experimentally based studies realized at watershed scale, especially in tile drained areas, are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of water pollution sources during hydrologically different situations is indispensable for adopting particular protective measures in various landscape zones and for setting the effective agricultural land management . However, findings obtained in experimentally based studies realized at watershed scale, especially in tile drained areas, are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…This research utilized selective sampling [31] and purposeful sampling [32] to identify academic journals in the water and forestry industries. A total of fifteen journals were examined that included: Manuscripts within these journals were examined for concrete examples of insights or practical lessons that could guide sport to establish a framework to adapt to contemporary climatic impacts., such as drivers of adaptations [33] and an overview of adaptation actions and their impacts on policy [34].…”
Section: Methodsmentioning
confidence: 99%
“…We need to plan today to adapt It has been noted that "climate change and extreme variability will force us to adapt to freshwater shortages, alterations in distribution" [33].…”
Section: Water Industry Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can see the negative impacts of these phenomena as frequent inundations, floods, erosive processes, or dramatic drops of water resource supplies. This will require changes in management of water resources in order to enhance accumulation and retention of water, optimally already in soil or in suitable watershed zones [17,18], emphasizing also the significance, versatility, and potential of the drainage systems. In some cases, the importance of drainage systems was rather underestimated and not adequately appreciated in CR and abroad.…”
Section: Management Of Agricultural Drainage Systemsmentioning
confidence: 99%